A stock-flow consistent model of inventories, debt financing and investment decisions - Gallo, Ettore; Serra, Gustavo Pereira [UNESP] (Elsevier, 2024)
The paper develops a Kalecki–Steindl–Minsky stock-flow consistent (SFC) model by including inventories, as well as firm's deposits and debt financing into the investment function. The role of investment decisions in shaping aggregate fluctuations over the business cycle is assessed by considering a model populated by five types of economic actors: workers, rentiers, firms, commercial banks and the central bank. Business cycle fluctuations are investigated assuming a deterministic steady growth path in the long period, in line with recent developments in heterodox growth theory. Next, we simulate the model, calibrating it for the US economy. Our main results confirm the relevance of inventory dynamics in economic cycles, similar to Metzler's (1941, 1947) analysis. First, inventory investment propagates shocks and affects the length of waves, deviation size and time to convergence. Second, expectations may determine whether there are oscillations or a steady convergence to the long-term trend. Third, we suggest that inventory investment accommodates rapid aggregate demand variations, although not presenting a multiplier effect.
Keywords: Business cycles; Debt; Internal finance; Inventories; Investment